IMPROVING TUDENTSâ WRITING SKILL IN RECOUNT TEXT BY USING PERSONAL LETTER AT EIGHT GRADE OF SMP TIGA HATI KEPENUHAN HULU - Hidayati, Etri; Sukma, Dian; Antoni, Rivi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research was conducted in order to improve studentsâ writing skill in recount text at eighth grade of SMP Tiga Hati Kepenuhan Hulu by using personal letter used a Classroom Action Research (CAR) which was conducted to solve the studentsâ problem in English Writing. The reseacher did two cycles in which each cycle consisted of plan, action, observation, and reflection. The qualitative data was gained by analyzing the fieldnote, observation sheet and interview, then quantitative data were obtained from the studentsâ writing score. The finding of this research indicated that the implementation of personal letter media was succesful since there was an improvement in studentsâ writing skill in recount text. The finding showed an improvement in studentsâ writing skill in recount text from the average of writing test recount text in cycle 1 was (60,85) to (73,50) the average of writing skill in cycle 2